(untitled) (Altre Modernità, 2021)
This essay analyses the ways in which James Joyce and Virginia Woolf addressed from a very early stage key issues related to contemporary posthumanist theories such as the question of animal speech and psychology. Both Joyce’s description of human-animal encounters in Ulysses and Woolf’s depiction of a sentient animal subject in Flush: A Biography at first present, and then subvert, the idea of the use of language as evidence of a human surpassing of the animal. By challenging preconceived notions of species distinctions, these authors ultimately decenter the human to focus instead on the centrality of animal subjectivity and sensory experience. While the question of a sharp divide between human and nonhuman animals along the axis of speech can be traceable to the anthropocentric tradition of western humanism and not least to such a possible source as Cervantes (whose novella “The Dialogue of the Dogs” is listed as part of both Joyce’s Trieste library and the library of Leonard and Virginia Woolf), the idea of expanding the typically modernist focus on inner life by also including other forms of subjectivity may have derived from the coeval, burgeoning fields of zoology, ethology and comparative psychology. Drawing from these sources and popular areas of knowledge which formed part of the cultural climate of the time, both Joyce and Woolf explore cross-species intersubjectivity in ways that shift the terms of representation away from anthropocentric views in order to affirm, blur and deny the boundaries between the human and the non-human.